2000
DOI: 10.1177/089686080002000640
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous VEGF Production by Cultured Peritoneal Mesothelial Cells from Patients on Peritoneal Dialysis

Abstract: Episodes of peritonitis 1.4±2.6 0.8±1.3 0.6 Accumulated glucose load (kg) 156.1±287 84.3±66 0.6 Creatinine MTC (mL/min) 11.7±9 10.1±3 0.7 Urea MTC (mL/min) 22.1±13 24.4±7.1 0.7 Ultrafiltration (mL/4 hr, 2.27% glucose) 650±339 540±124 0.5 VEGR = vascular endothelial growth factor; PD = peritoneal dialysis; MTC = mass transfer coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Recently, important contributions from cell biology and histopathology studies have helped us to understand the pathophysiology of the peritoneal membrane response. [12][13][14][15][16][17][18] Epithelial-to-mesenchymal transition (EMT) of MC has been identified as a key process leading to peritoneal fibrosis with functional deterioration. 19,20 Concerning human histopathology studies, it must be remarked that most peritoneal biopsy studies have been based on PD patients with long-term treatment and peritoneal functional problems, specifically UF failure.…”
mentioning
confidence: 99%
“…Recently, important contributions from cell biology and histopathology studies have helped us to understand the pathophysiology of the peritoneal membrane response. [12][13][14][15][16][17][18] Epithelial-to-mesenchymal transition (EMT) of MC has been identified as a key process leading to peritoneal fibrosis with functional deterioration. 19,20 Concerning human histopathology studies, it must be remarked that most peritoneal biopsy studies have been based on PD patients with long-term treatment and peritoneal functional problems, specifically UF failure.…”
mentioning
confidence: 99%
“…Cultured mesothelial cells synthesize various chemokines, prostaglandins and growth factors [ 29 ]. Some are produced constitutively, like vascular endothelial growth factor (VEGF) [ 30 ] and cancer antigen 125 (CA 125) [ 31 ]. Others, like interleukin-6 (IL-6) and IL-8, are produced after stimulation with chemokines [ 32 , 34 ].…”
Section: Mechanisms Of Ultrafiltration Failurementioning
confidence: 99%
“…In vitro studies have shown that cultured mesothelial cells are able to produce various cytokines, chemokines, and prostaglandins (15). Most inflammatory mediators, like interleukin (IL)‐6 and IL‐8 are produced after stimulation with tumor necrosis factor‐α (TNF‐α) or IL‐1; others like vascular endothelial growth factor (VEGF) and cancer antigen 125 (CA125) are released constitutively (16,17). All these substances, some of which are vasoactive, can be detected in peritoneal effluent of PD patients (18).…”
Section: Types Of Fast Transport Statusmentioning
confidence: 99%